2008
DOI: 10.1111/j.1741-3729.2008.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Change in Families Following the Home‐Start Parenting Program: Clinical Significance and Predictors of Change

Abstract: The aim of the present study was to examine whether improvements obtained after a home-based parenting intervention reflected meaningful and significant changes for a sample of Dutch mothers. The results showed that Home-Start mothers demonstrated reliable changes in well-being and enhanced parenting behaviors compared to both a comparison and a norm group of mothers. At posttest, a substantial number (39 -84%) of the HomeStart mothers functioned at a level equivalent to that of a community group. The most rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In a recent quasi experimental study by Asscher, Hermanns and Deković (2008) positive effects were reported by mothers: improvements in maternal competence, less depressive feelings, more consistent parenting behaviour and decreased negative controlling behaviour. Moreover, Asscher, Dekovic, Prinzie, and Hermanns (2008) showed that results were of clinical significance, since at post-test a substantial number (39% to 84%) of the Home-Start mothers functioned in the domains of maternal well-being, parenting behaviour and child behaviour at a level equivalent to that of a community sample. Dekovic et al(2010) tested the mechanisms of change of the HomeStart and found that intervention results were consistent with the hypothesised intervention model: Home-Start induced changes in feelings of parental competence which in turn predicted changes in parenting.…”
mentioning
confidence: 99%
“…In a recent quasi experimental study by Asscher, Hermanns and Deković (2008) positive effects were reported by mothers: improvements in maternal competence, less depressive feelings, more consistent parenting behaviour and decreased negative controlling behaviour. Moreover, Asscher, Dekovic, Prinzie, and Hermanns (2008) showed that results were of clinical significance, since at post-test a substantial number (39% to 84%) of the Home-Start mothers functioned in the domains of maternal well-being, parenting behaviour and child behaviour at a level equivalent to that of a community sample. Dekovic et al(2010) tested the mechanisms of change of the HomeStart and found that intervention results were consistent with the hypothesised intervention model: Home-Start induced changes in feelings of parental competence which in turn predicted changes in parenting.…”
mentioning
confidence: 99%
“…Our findings emphasize the significance of shared decision-making and patient autonomy in the clinical encounter, acknowledging that informed patients are better equipped to actively participate in their orthodontic journey. This aligns with the evolving landscape of healthcare, where transparency not only serves ethical principles but is also instrumental in fostering a patient-centered approach and optimizing overall treatment outcomes [78,79].…”
Section: Discussionmentioning
confidence: 73%
“…By examining not just the comparable differences between groups, but also the significance of change over time, it was found there was significant change in mothers' wellbeing and in depression levels. Parental behavior improved significantly according to parents' reports, although no change was identified in most observational parental measures [49].…”
Section: Volunteer-based Home Visiting Interventionsmentioning
confidence: 90%